2023
DOI: 10.3390/vaccines11020250
|View full text |Cite
|
Sign up to set email alerts
|

Community Perception and Attitude towards COVID-19 Vaccination for Children in Saudi Arabia

Abstract: Introduction: Vaccines are an important part of the COVID-19 pandemic response plan. This study was undertaken to find out the percentage of supporters in the Saudi population for COVID-19 vaccination among children, and to assess the study population’s perceptions towards COVID-19 vaccination among children. Material and Methods: This nationwide study adopted a cross-sectional survey of adult participants, conducted by trained medical students. The anonymous questionnaire was published on social media tools. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…A recent study conducted in Saudi Arabia reports that about 12.8% of children have not received the vaccination, 55% of parents have some sort of hesitation and 32.2% of parents did not hesitate before vaccinating their children against COVID-19 [ 10 ]. Vaccine newness, as a reason for hesitating to get vaccinated, was most reported among non-vaccine supporters in another study from Saudi Arabia [ 11 ]. The side effects of the COVID-19 vaccine are the most important barrier to vaccine acceptance [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study conducted in Saudi Arabia reports that about 12.8% of children have not received the vaccination, 55% of parents have some sort of hesitation and 32.2% of parents did not hesitate before vaccinating their children against COVID-19 [ 10 ]. Vaccine newness, as a reason for hesitating to get vaccinated, was most reported among non-vaccine supporters in another study from Saudi Arabia [ 11 ]. The side effects of the COVID-19 vaccine are the most important barrier to vaccine acceptance [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies developed in other countries have also reported side effects from the COVID-19 vaccine as being the most common concern expressed regarding both children under 5 years and 5-12 years [11,12]. Another study evaluating COVID-19 vaccine uptake among healthcare workers in Albania observed that staff living in households with ≥4 members who were supposed to have dependent children in the house were less likely to receive a third COVID-19 vaccine dose compared with two-person households [13].…”
Section: Discussionmentioning
confidence: 99%
“…This result is agreement with the result of 13. . Table (2) Association between overall attitudes of male and female toward covid-19 vaccination and their demographic data. The present study shows the association between the overall attitudes of adult community toward COVID-19 vaccination and their demographic data were a significant association (P<0.05) except: gender in which there was a non-significant association (P>0.…”
Section: Itemsmentioning
confidence: 99%